Implementasi Pendidikan Karakter melalui Pembiasaan Menyanyikan Lagu Wajib Nasional pada Siswa Kelas Atas di SDM 21 Surakarta - Sari, Dwi Novita, Dra. Ratnasari Diah Utami, M.Si., M.Pd (2016)
This study aims to describe: 1) Implementation of character education nationalism and national spirit through singing the national anthem in HR 21 Surakarta. 2) Barriers to implementation of character education nationalism and national spirit through singing the national anthem in HR 21 Surakarta. 3) The solution to overcome obstacles in the implementation of character education nationalism and national spirit through singing the national anthem in HR 21 Surakarta. This type of research is qualitative research (Qualitative Research). The informants are students upscale and upscale guardian. Data collection techniques used were observation, interviews, and documentation. Data were analyzed through data reduction measures and conclusion. Mechanical data validity checking is done by triangulation of sources and techniques. The results showed that in HR 21 Surakarta has implemented character education nationalism and national spirit through singing the national anthem is good. Although there is little resistance, but the teacher has given a solution so that these obstacles can be minimized.